PENGARUH PEMBERIAN KOMPOS ISI RUMEN SAPI DAN PUPUK NPK TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) PADA TAHAP PEMBIBITAN UTAMA (MAIN NURSERY) - Ranti Purnamasari; Ardian '; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research was to know the interaction of giving composted contains cow rumen and NPK fertilizer, main factor are contains cow rumen and NPK fertilizer and to get the best treatment to supporting the seedling growth of palm oil (Elaeis guineensis Jacq) on main nursery. This research had been conducted on the experimental garden, Faculty of Agriculture, University of Riau from May to September 2015. This research had been conducted in 4 x 4 factorial experiment arranged with completely randomized design consisted of two factors. The first factor is the of composted contains cow rumen consisted of 4 levels are 25 g/plant, 50 g/plant, 75 g/plant, and 100 g/plant and the second factor is the dose of NPK fertilizer consist of 4 levels are 1,5 g/plant, 2,0 g/plant, 2,5 g/plant and 3,0 g/plant. In this research there are 16 combinations treatment with 3 replications thus obtained 48 experimental units. Each experimental unit consisted of two seedling so total number are 96 seedlings. Observation were carried out are increase of plant height, increase of leaf number, increase of diameter hump and leaf wide. The result showed that the interaction composted contents cow rumen and NPK fertilizer gave unreal effect. Composted contents cow rumen treatment and NPK fertilizer treatment were gave unreal effect. To get maximum result need continuous research with increasing dose of composted content cow rumen and NPK fertilizer.   Keywords : Composted contents cow rumen, palm oil, NPK fertilizer